Evaluation of mechanical characterization and deformation for filaments under sliding behavior - IZUMI, Takahiro; HANAKI, Koushu; KURASHIKI, Tetsusei; MUKOYAMA, Kazutaka; LI, Xingsheng (Journal of Textile Engineering, 2024)
Filaments used in textile products have many design parameters such as length, diameter, tip shape, material properties, etc. In order to design and develop the products efficiently that satisfy the desired functions, it is important to estimate the mechanical properties of filaments with various design parameters and to quantify the effects of design parameters on the mechanical behavior. In this study, we focused on as one of the design parameters of textile products, and evaluated the effects of this parameter on the mechanical properties of filaments under the sliding behavior based on the numerical and experimental approach. The results had shown that the difference in the tip shape of filaments affects the load value applied to the contacting body. It was also shown that the difference in the tip shape affected the deformation behavior. The difference of the tip shape was caused by the strain energy density of filaments during sliding movement. We believed that the results obtained in this study would be useful for the design and development of textile products efficiently.